Infant and young child feeding guidelines: awareness amongst mothers and practices followed - Dubewar, Shraddha; Ahmed, Sarfaraz; Tambe, Saleem H.; Chavan, Arvind (International Journal of Contemporary Pediatrics, 2018)
Background: Globally if the exclusive breast feeding is adopted there is up to 15% reduction in the mortality of under five children. At the same time proper “complementary feeding practices” leads to up to 10% more decrease in the mortality rates. The objective of this study was to study the infant and young child feeding practices among mothers Methods: This was an observational study, conducted at Aditya Hospital, Hyderabad in the period duration of 2012-2013. All children upto 24 months of life and their mothers were included in the study. Results: Most common reasons given by the mothers were pain in the stitches and discomfort and anesthesia effect due to lower segment caesarean section (LSCS) (70%). it was found that there was no significant correlation between education status of mother and time of initiation of breast feeding (P=0.6). it was found that there was no statistical significance between giving of pre-lacteals according to educational status of mothers. Almost 60% (n=64) of the mothers were appropriate in starting complementary foods at the age of 6 months. Conclusions: Women need to be educated separately with knowledge regarding of appropriate feeding practices so that both mothers and babies benefit from it; leading further to a healthy nation.